Multi Level Pengabdian Masyarakat Program Studi Tadris Matematika Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi melalui Rumah Pintar Integrasi - Vinny Yuliani Sundara; Zawaqi Afdal Jamil; Rini Warti; Ali Usmar (Jurnal Pengabdian Pada Masyarakat, 2021)
MULTI LEVEL COMMUNITY SERVICE DEPARTEMENT OF MATHEMATICS EDUCATION AT THE STATE ISLAMIC UNIVERSIY OF SULTHAN THAHA SAIFUDDIN JAMBI THROUGH RUMAH PINTAR INTEGRASI. Departement of Mathematics Education has a forum for community service namely Rumah Pintar Integrasi (RPI). The lecture method is used for multi-level knowledge transfer. The implementation of this community service program has produced results, namely the formation of the RPI with the Decree of the Dean of the Faculty of Tarbiyah and Teachers of the State Islamic University of Sulthan Thaha Saifuddin Jambi Number 223 Year 2019 regarding the Establishment of RPI Management and was officially launched and symbolized cutting ribbon by Deputy Dean II. Activities to improve understanding of mathematical concepts have been carried out and obtained results that there is a significant increase between the pretest and posttest scores. The community service activity of the Department of Mathematics Education was carried out in January 2020 with the concept of students giving free tutoring to "SD / MI" schools in preparation for the UN. There are around 200 students spread in 147 elementary schools in Jambi Province and even in other provinces. implemented multi-level community service in mathematics education majors.